1998
DOI: 10.1046/j.1471-4159.1998.71010394.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Increasing Gestational Age and Placental Restriction on Tyrosine Hydroxylase, Phenylethanolamine N‐Methyltransferase, and Proenkephalin A mRNA Levels in the Fetal Sheep Adrenal

Abstract: We have demonstrated that there are differential changes in the levels of tyrosine hydroxylase (TH), phenylethanolamine N-methyltransferase (PNMT), and proenkephalin A (Pro Enk A) mRNA in the fetal sheep adrenal during late gestation. Adrenal TH mRNA:18S rRNA ratios increased between gestational days 100 (0.98 ±0.13; n = 6) and 125 (1.40 ±0.15; n = 6) and then decreased, whereas adrenal PNMT mRNA:18S rRNA ratios increased regularly between gestational days 100 (0.08 ±0.01) and 146 (0.17 ±0.03). The ratio of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Fetuses of smokers are subjected to chronic hypoxia in utero because carbon monoxide freely crosses the placenta, binding avidly to sites that normally carry and release oxygen to the tissues (19). In sheep, chronic fetal hypoxemia is associated with a reduction of adrenal mRNA levels of the epinephrine-synthesizing enzyme phenylethanolamine N-methyltransferase (20). If this also occurs in humans, a reduction in phenylethanolamine Nmethyltransferase could account for our finding that maternal smoking had the greatest impact on reducing epinephrine concentrations in smokers compared with nonsmokers.…”
Section: Discussionmentioning
confidence: 99%
“…Fetuses of smokers are subjected to chronic hypoxia in utero because carbon monoxide freely crosses the placenta, binding avidly to sites that normally carry and release oxygen to the tissues (19). In sheep, chronic fetal hypoxemia is associated with a reduction of adrenal mRNA levels of the epinephrine-synthesizing enzyme phenylethanolamine N-methyltransferase (20). If this also occurs in humans, a reduction in phenylethanolamine Nmethyltransferase could account for our finding that maternal smoking had the greatest impact on reducing epinephrine concentrations in smokers compared with nonsmokers.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the enzymes responsible for the biosynthesis of catecholamines in the adrenal medulla has been examined during gestation in fetal sheep (3). Levels of mRNA for tyrosine hydroxylase (TH) in the medulla increase coincident with the onset of splanchnic innervation (ϳ100 -125 dGA) and subsequently decline after ϳ140 dGA.…”
mentioning
confidence: 99%
“…Levels of mRNA for tyrosine hydroxylase (TH) in the medulla increase coincident with the onset of splanchnic innervation (ϳ100 -125 dGA) and subsequently decline after ϳ140 dGA. Phenylethanolamine N-methyltransferase (PNMT) mRNA exhibits a slightly different pattern of expression compared with TH, with a progressive increase slightly earlier in gestation at ϳ80 -100 dGA and an additional larger increase near term (ϳ140 -146 dGA) (3). The noted increase in PNMT near term in the adrenal medulla occurs coincident with increased adrenal epinephrine content and increased basal epinephrine release from perfused adrenal glands (9,12).…”
mentioning
confidence: 99%
“…Regulation of phenylethanolamine N-methyltransferase (PNMT), the enzyme responsible for catecholamine production, is classically thought to be affected by glucocorticoids in most species (21,166,179), with increases in glucocorticoid stimulating PNMT expression in adrenomedullary cells (105,159,174). However, in growth restriction models of hypoxia via carunclectomy, Coulter et al (44) showed that dopamine ␤-hydroxylase (DBH) and encephalin-containing peptide immunostaining was decreased, and Adams et al (4) observed decreased PNMT expression. In high-altitude induced long-term hypoxia (LTH), fetal plasma epinephrine concentrations were shown to be attenuated in response to superimposed acute hypoxia compared with normoxic controls despite similar basal plasma catecholamine levels, with no changes in norepinephrine (90).…”
Section: Chronic Hypoxiamentioning
confidence: 99%
“…In larger mammalian fetuses, these systems exhibit maturation in late gestation and serve similar roles, providing the fetus with the means to respond to intrauterine stressors. Activation of these two mechanisms leads to rapid glucose, renal, and cardiovascular changes (35,62,88,180) as well as slower adaptive modifications of gene expression to combat potential long-term effects (3,4,51,120,181). Although these responses to hypoxic stress may often be beneficial acutely, they have the potential to be deleterious, especially under sustained periods of hypoxic stress.…”
mentioning
confidence: 99%